Toward Automated Dynamic Malware Analysis Using CWSandbox. - Willems, C. (IEEE Security and privacy : building confidence in a networked world)
Malware is notoriously difficult to combat because it appears and spreads so quickly. In this article, we describe the design and implementation of CWSandbox, a malware analysis tool that fulfills our three design criteria of automation, effectiveness, and correctness for the Win32 family of operating systems